The effect of post traumatic stress disorder on the school performance of adolescents - Amod, Yaseera (My University, 1999)
The aims of this study were: 1) To determine the relationship between Post Traumatic Stress and its impact on the school performance of adolescents. 2) To determine whether exposure to violence impacts on school performance. the level of Post Traumatic Stress Disorder was ascertained via a questionnaire. (Abbreviation abstract)
A dissertation submitted to the Faculty of Arts, University of the Witwatersrand, Johannesburg for the Degree Master of Arts (Educational Psychology)
Keywords: Post-traumatic stress disorder in children; Adolescent psychology--South Africa; School children--South Africa